CHANGES IN ORGANIZATIONAL STRUCTURE AND WORK CULTURE AT THE OFFICE OF THE MINISTRY OF RELIGION OF ACEH JAYA REGENCY (Study on the Impact of Bureaucratic Reform Policies through Equalization of Positions) - Idris Suteja; Syafei Ibrahim; Kridawati Sadhana (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Initial findings in the field show that there is resistance from some employees who feel that they have lost status or influence due to a change in position. Some employees also experience confusion about new roles and responsibilities in functional positions, which has an impact on decreased work motivation and organizational effectiveness. The purpose of this study is to determine the Impact of Bureaucratic Reform Policy Through Equalization of Positions with changes in organizational structure and work culture at the Office of the Ministry of Religion of Aceh Jaya Regency. The grand theory used is William N Dunn's theory of policy evaluation. The research method used is a qualitative research method based on the philosophy of postpositivism or interpretation. The focus of his research is Changes in Position Structure, Organizational Culture and Bureaucratic Reform Policy. Research results: Overall, the implementation of bureaucratic reform through equalization of positions at the Office of the Ministry of Religion of Aceh Jaya Regency has had an impact on the organizational structure and work culture. However, these changes are not fully effective because they are faced with a number of internal obstacles, such as employee unpreparedness, weak socialization, and not optimal support systems. Therefore, a more adaptive, participatory, and based on strengthening human resources is needed so that the goal of bureaucratic reform can really be realized at the regional level. The main novelty of this study lies in the comprehensive approach used, the local context raised, and the depth of analysis of the experience of employees as the main actors of bureaucratic reform. This dissertation makes an important contribution in bridging the gap between macro policy and the micro-realities of bureaucracy in the field.